ANALISIS INTEGRASI BURSA SAHAM ASEAN 5 - Ardina Puspitasari; Hermanto Siregar; Trias Andati (IPB University, 2015)
This study aimed to analyze the integration of the stock markets of ASEAN 5 (Indonesia, Malaysia, Singapore, Thailand, and the Philippines) associated with the event of dropped world oil prices in 2014. This study using Vector Error Correction Model (VECM) to analyze market integration 5 stocks with variable stock market. In this study uses a dummy variable of oil price with the value of 0 for the period 2009 to 2013 where world oil prices are still stable and the value of 1 for the period 2014 to 2015 where a decline in world oil prices. Results from this study shows that there is a relationship between the stock market cointegration ASEAN 5 during the study period that’s mean that there is integration among ASEAN 5 stock markets. Indonesia's stock market is influenced by Thailand and Singapore in the long term. Dummy variables significantly influence the JCI during the short term.